การเปิดรับข่าวสารกับการเข้าร่วมในโครงการเกษตรทฤษฎีใหม่ ตามแนวพระราชดำริของเกษตรกรในเขตอำเภอเก้าเลี้ยว จังหวัดนครสวรรค์ - ดวงหทัย วงษ์ราช (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The purpose of this research was to examine the correlation among media exposure, knowledge, attitude and participation in the Royally-initiated New Theory Project of farmers in Amphoe Kao Lieo, Nakhon Sawan Province. Questionnaires were used to collect the data from a total of 370 samples. Frequency, percentage, mean, t-test, One-Way ANOVA, Pearson s Product Moment Correlation Coefficient and Multiple Regression Analysis were employed for the analysis of the data. SPSS for Windows was used for data processing. The results were as follows: 1. Farmers with different demographic characteristics participated in the Royally-initiated New Theory Project differently. 2. Exposure to newspaper, agricultural officials and specialized media positively correlated with knowledge of the Royally-initiated New Theory. 3. Exposure to specialized media positively correlated with attitude toward the Royally-initiated New Theory. 4. Exposure to mass media, interpersonal media and specialized media positively correlated with participation in the Royally-initiated New Theory Project. 5. Knowledge of the Royally-initiated New Theory positively correlated with attitude toward the Royally-initiated New Theory. 6. Knowledge of the Royally-initiated New Theory positively correlated with participation in the Royally-initiated New Theory Project. 7. Attitude toward the Royally-initiated New Theory positively correlated with participation in the Royally-initated New Theory Project. 8. Exposure to specialized media was able to explain the participation in the Royally-initiated New Theory Project most